Rearing of Metasiriella kitaori (Mysidacea) under laboratory condition - Galope , Della Grace Quinte (Iloilo University of the Philippines in the Visayas., 1990)
This exploratory study was conducted to elucidate some aspects of the biology of MetasiriellaKitaroi (Mysidacea), such as : 1) ife history and stages of Development ; 2) Food and Feeding ; 3) Response to salinity ; and 4) Size Frequency Distribution in the Pond. Gravid Metasiriellakitaroi collected from the UPV-BAC prawn pond produced 3-7 young in the laboratory. The young, when releasedd within 1 to 5 days from the marsupium, looked like miniature adults. The laboratory-produced M. Kitaroi young with body lenght of 1.8 - 2.5 mm reached early stages of maturity at body lenght of 4.8 - 5.8 mm after 12-14 days and repproduced at an average body lenght og 6.0 mm after 17 to 21 days with lumut as food under laboratory conditions. Feeding experiment showed that M. kiaroi attained relatively high survival n lumut (40%) than in Tetraselmis sp. (30%), Chlorella virginica (25%), Chaetoceros calcitran (20%) and Keletonema costatum (12.5%). M. kitaroi was observed to be a filter-feeder as well as a scavenger. Cannibalism was likewise exhibited by the animal. Better survival and growth of M. Kitaroi were obtained at 35 ppt than 25 ppt and 15 ppt. Avergae percentage of survival was consistently higher at 35 ppt (70.33% and 70%) than at 25 ppt (48.1% and 66.6%) and 15 ppt (40.7% and 50%). Likewise, average body lenght obtained was slightly higher at 35 ppt (5.39 and 4.8 mm) than at 25 ppt (5.29 and 4.25 mm) and 15 ppt (4.9 and 4.3 mm). However differences in percentage of survival and growth were not statistically significant. Sapling for size frequency distribution during the month of September showed that UPV-BAC prawn pond was inhabited mostly by adult M. kitaroi with body length ranging from 5.45 to 6.35 mm.
Thesis (M.S. Fisheries-Aquaculture) -- Miagao, Iloilo : University of the Philippines in the Visayas, March 1990.
Keywords: Mysidacea